Identification of capsaicin and dihydrocapsaicin in the oleoresin extract obtained from panca chili (Capsicum chinense) - Baldeón-Apaestegui, Silvana (2017)
Oleoresin is a liquid extract which is obtained from chili and peppers of genus Capsicum, to be used in the food industry very often. This paper describes the oleoresin extraction from aji panca chili pepper by the Soxhlet method. The yield of oleoresin was 22,77 % using ethanol as extraction solvent. The capsaicinoids ―capsaicin and dihydrocapsaicin― present in the oleoresin were identified in ethanol at a maximum 281 nm wavelength.